HUBUNGAN KADAR HEMOGLOBIN IBU HAMIL BERDASARKAN POLA MAKAN DI RUMAH SAKIT ANNISA PEKANBARU - Hotmauli Hotmauli; Eli Yusrita; Erick Caesarrani; Brilian Dini (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2023)
Hemoglobin is a protein that binds oxygen, carbon dioxide and protons. The function of hemoglobin is to transport oxygen from the lungs throughout the body and gives color to red blood cells. Factors triggering a decrease in hemoglobin levels are unhealthy eating patterns and pregnancy. During pregnancy, a woman contains an embryo, which starts from the embryo is formed until the fetus is born. Physical changes in pregnant women, such as body weight, also change in body attitude. Pregnant women also experience fatigue, so sleep is very important. The purpose of this study was to determine hemoglobin levels in pregnant women at Annisa Pekanbaru Hospital based on sleep quality. Using cross sectional method. Using 33 pregnant women respondents with poor sleep quality totaling 22 people and good quality totaling 11 people. The hemoglobin level of pregnant women is in the range of 9.0 – 11.7 g/dL. The conclusion that can be drawn is that pregnant women with good sleep quality have an average hemoglobin level of 10.3 g/dl, while pregnant women with poor sleep quality have an average hemoglobin level of 9.4 g/dL.